1, 3-dimethyl-6-nitroacridine derivatives induce apoptosis in human breast cancer cells by targeting DNA. (1st February 2019) - Zhou, Qian; Wu, Hongshuai; You, Chaoqun; Gao, Zhiguo; Sun, Kai; Wang, Mingxin; Chen, Fanghui; Sun, Baiwang
Abstract: The acridine derivatives can interact with the double-stranded DNA, which is regarded as the biological target of the anticancer drugs in cancer treatment. We designed and synthesized a new series of 1, 3-dimethyl-6-nitroacridine derivatives as potential DNA-targeted anticancer agents. These compounds could partially intercalate into the calf thymus DNA, differing from the parent acridine. The results showed that the substitutions of the acridine ring had great effect on DNA binding affinity. The binding constants determined by UV-vis spectroscopy were found to be 10 5  M −1 grade. Anticancer activity of these compounds was screened using MTT assay. Most compounds inhibited 50% cancer cell growth at concentration below 30 μM, the results were consistent with the DNA binding ability. Compounds1 and6 were found to have more effective cytotoxicity, especially in human breast cancer cell lines. To investigate the action mechanism, we studied cell apoptosis, morphological changes, and cell cycle distribution in MCF-7 and MDA-MB-231 cells. Compounds1 and6 caused MCF-7 and MDA-MB-231 cells death due to apoptosis, and induced cell apoptosis in a dose-dependent manner. They also had significant effect on cell cycle progression and arrested cell cycle at G2/M phase. The results demonstrated that compounds1 and6 are promising candidates for cancer treatment.